The influence of Leadership Style and Work Motivation on Employee Performance at PT Sai Apparel Industries Semarang - Annisa Widhi Kinasih; Sugiyanta - Sugiyanta; M - Nahar (JOBS (Jurnal Of Business Studies), 2020)
The problem of the sewing department of PT Sai Apparel Industries Semarang was it never reached the production target in 2019. This purposes of this research are to find out influence of leadership style and work motivation on employee performance at PT Sai Apparel Industries Semarang. Dependent variabels in this reseach is leadership style and work motivation while dependent variables is employee performance. Data collection used are questionnaires, interview, and literature review. The sample in this study are 95 employees of the sewing devision at PT Sai Apparel Industries Semarang. The data analysis technique used multiple regression. The result of multiple regression indicated that leadership style and work motivation all of them had positive influence on employees performance. The most dominant variable that influence the employee performance is the work motivation. While from the result of determination coeffiecient (Adjusted R Square) indicated that leadership style and work motivation affects employee performance 0.597 or 59.7%. While 40.3 or 40.3% influenced by other variables not examined in this research